Optimalisasi Digital Marketing Sebagai Strategi Pemasaran Pada UMKM Dapur Keysha di Desa Mranggonlawang - Alodiya Sifa Meiyantika; Nurul Azizah (Yayasan Daarul Huda Kruengmane, 2023)
Sophistication in the field of information technology today can divert marketing trends that were previously traditional and are now turning to digital marketing. Marketing that utilizes advances in digital technology has a trending language, namely Digital Marketing or Digital Marketing. Digital Marketing is carried out through interactive and integrated marketing that allows communication and transactions between business actors, market intermediaries and consumers at any time. and transactions between business actors, market intermediaries, and consumers at any time. With digital marketing, of course it will make it easier for target consumers to find the product they are looking for just by accessing the internet. One of the SMEs in Mranggonlawang Village, Dapur Keyhsa has a problem with its market which is still quite limited, they only take advantage of their sales promotion by word of mouth and acquaintances so that the products from Dapur Keysha are not well known by outsiders. This activity aims to expand the marketing system of Dapur Keysha so that it can expand the scope of its business goals. The method in this activity is to provide socialization and assistance in making social media, e-commerce, creative content and MSME websites for Dapur Keysha. From this digital marketing optimization activity, it was obtained the creation of an Instagram social media account by utilizing its various features, the creation of a Shopee e-commerce account, and the creation of a Google Business account for Dapur Keysha.